Life-Cycle Worker Flows and Cross-country Differences in Aggregate Employment - Créchet, Jonathan; Lalé, Étienne; Tarasonis, Linas (Université d'Ottawa | University of Ottawa, 2023)
We propose new data moments to measure the role of life-cycle worker flows between employment, unemployment and out of the labor force in shaping cross-country differences in aggregate employment. We then show that a suitably extended version of the Diamond-Mortensen-Pissarides model can capture well these data moments. Two features of the model are crucial for this result: heterogeneity in match quality and endogenous search intensity. We examine the implications of this model for the sources of employment dispersion across Europe's largest countries, assessing the contribution of factors related to (i) the production technology, (ii) search, and (iii) policies. The sources of cross-country employment dispersion differ substantially across ages. Technology factors account for most of the employment variance of youths and prime-age workers, whereas search and policies are the main drivers of employment differences for older individuals.
Keywords: Employment; Labor Force Participation; Life cycle; Unemployment; Worker Flows; Labor Market Institutions